Effects of MS-31-038, a Novel Na+-H+ Exchange Inhibitor, on the Myocardial Infarct Size in Rats after Postischemic Administration - Banno, Hitoshi; Fujiwara, Junya; Hosoya, Junko; Kitamori, Takashi; Mori, Haruki; Yamashita, Hiroyuki; Ikeda, Fumiaki (Arzneimittelforschung, 1999)
The abilities of 2-(2-methylphenyl)-5,7-dimethoxy-4-quinolyl carbonylguanidine dihydrochloride (CAS 181048-29-3, MS-3l-050) and 2-phenyl-8-(2-methoxyethoxy)-4-quinolyl carbonylguanidine bismethanesulfonate (CAS 181048-36-2, MS-31-038) in inhibiting Na+-H+ exchange, ischemiaand reperfusion-induced injury were determined and compared with those of 4-isopropyl-3-methylsulfonylbenzoyl guanidine methanesulfonate (CAS 159138-81-5, IMGM), a selective inhibitor of Na+-H+ exchange. MS-31-050 and IMGM exhibited comparable inhibitory effects on Na+-dependent pH recovery and antiarrhythmic effects during ischemia in anesthetized rats. In rats subjected to ischemia and reperfusion, MS-31-050 (10 mg/kg i.v.) significantly reduced the infarct size when given prior to the onset of ischemia. However, postischemic treatment with either MS-31-050 or IMGM failed to protect reperfused hearts. In contrast, MS-31-038 reduced the infarct size dramatically from 65.4 ± 7.4% in control to 29.9 ± 11.6% at 3 mg/kg and 9.8 ± 3.4% at 10 mg/kg even when administered before the onset of reperfusion. These results suggest the beneficial effects of Na+-H+ exchange inhibitors on myocardial ischemia/reperfusion injury.
Keywords: CAS 181048-29-3 CAS 181048-36-2 Ischemia 2-(2-Methylphenyl); -5,7-dimethoxy-4-quinolyl carbonylguanidine dihydrochloride; MS-31-038, effect on myocardial infarct size, rat; Na+-H+ exchange; 2-Phenyl-8-(2-methoxyethoxy)-4-quinolyl carbonylguanidine bismethanesulfonate; Reperfusion arrhythmia